Analisis Model Sistem Antrian Pada Pelayanan Konsumen Mie Gacoan Cabang Pancing Kota Medan - Yohana Sitorus; Sukma Dermawan Saragih; Wahyuni Susi Sulastri Berasa; Sisti Nadia Amalia (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2024)
This research aims to analyze the queuing system model for consumer service at Mie Gacoan Pancing Branch, Medan City. With the increasing popularity of Mie Gacoan, there has been a significant increase in the number of customers, resulting in long queues and long waiting times. This research uses observation and interview methods to collect data regarding the number of customers, arrival time, service time, and number of available waiters. The data is then analyzed using the M/M/1 and M/M/c queuing models to determine queue characteristics such as average queue length, average waiting time in the queue, and waiter utility. The analysis results show that the M/M/c queuing model is more effective in reducing waiting time and queue length compared to the M/M/1 model. By increasing the number of waiters, service efficiency can be increased, thereby increasing customer satisfaction. This research provides strategic recommendations for the management of Mie Gacoan Pancing Branch in optimizing the queuing system to provide better service to consumers.